2010
DOI: 10.1017/cbo9780511711961
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Foundations and Biomechanics of the Digestive System

Abstract: Mathematical modelling of physiological systems promises to advance our understanding of complex biological phenomena and pathophysiology of diseases. In this book, the authors adopt a mathematical approach to characterize and explain the functioning of the gastrointestinal system. Using the mathematical foundations of thin shell theory, the authors patiently and comprehensively guide the reader through the fundamental theoretical concepts, via step-by-step derivations and mathematical exercises, from basic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 112 publications
1
9
0
Order By: Relevance
“…It is observed that both the normal and frictional forces are not uniform because there are many microstructures on the intestinal surface, which is not smooth at all when observed under a microscope. 23 Within the velocity range considered, the sliding friction force is lower for a higher sliding velocity ( Figure 5(b)), which is similar to the behavior of the sliding friction on some other tissues. 24 For a viscoelastic material, the change in the normal force causes the change in the COF.…”
Section: Methodssupporting
confidence: 75%
“…It is observed that both the normal and frictional forces are not uniform because there are many microstructures on the intestinal surface, which is not smooth at all when observed under a microscope. 23 Within the velocity range considered, the sliding friction force is lower for a higher sliding velocity ( Figure 5(b)), which is similar to the behavior of the sliding friction on some other tissues. 24 For a viscoelastic material, the change in the normal force causes the change in the COF.…”
Section: Methodssupporting
confidence: 75%
“…In terms of the distribution of mechanical forces, the nongastric organs are biomechanically considered "soft cylindrical shells" (cf. Gregersen, 2003;Miftahof and Nam, 2010). Practically, in these "shells," forces tend to distribute and dissipate down as well as up the lengths of the tubes, and tension and stretch of the wall typically remain reasonably well correlated.…”
Section: Functions Of Gastric Imasmentioning
confidence: 99%
“…When food is ingested, the stomach reflexively executes motor patterns to receive, store, grind, mix, and eventually empty nutrients into the intestines for subsequent digestion and absorption (Mayer, 1994;Camilleri, 2006). During these coordinated programs, the organ is subject to multiple forces (see, e.g., Gregersen, 2003;Miftahof and Nam, 2010), and tension and stretch of gastric muscle fibers are often independent. For example, during a meal, as nutrients are ingested in Author Manuscript successive swallows, the proximal stomach relaxes incrementally in a progression of vagovagally mediated adjustments.…”
Section: Functions Of Gastric Imasmentioning
confidence: 99%
See 1 more Smart Citation
“…Most experiments are being conducted on animal tissues and only a few studies are related to human organs (Alexander 1971(Alexander , 1976Andersson et al 1989;Bider et al 2001;Coolsaet et al 1975aCoolsaet et al ,b, 1976Egorov et Al 2002;Finkbeiner 1999;Gloeckner 2003;Gloeckner et al 2002;Kondo and Susset 1973;Kondo et al 1972;Korossis et al 2009;Miftahof and Nam 2010;Nagatomi et al 2008;Parekh et al 2010;Sacks 2000;van Mastright and van Duyl 1978;van Mastrigt and Nagtegaal 1981;Venegas et al 1991;Wagg and Fry 1999;Wognum 2010). We have only recently started gaining insight into uniaxial and biaxial biomechanical characteristics of the gastrointestinal tract and the bladder.…”
Section: Bladder Substitutesmentioning
confidence: 99%